2011
DOI: 10.1002/btpr.607
|View full text |Cite
|
Sign up to set email alerts
|

Continuous rhamnolipid production with integrated product removal by foam fractionation and magnetic separation of immobilized Pseudomonas aeruginosa

Abstract: Increasing interest in biological surfactants has led to intensified research directed at more cost-efficient production of biosurfactants, relative to traditional surface-active components based on petrochemical feedstocks. This publication will focus on a new integrated process for continuous rhamnolipid (RL) production. RL was synthesized by Pseudomonas aeruginosa DSM 2874 and was continuously removed in situ by foam fractionation. To prevent loss of the biocatalyst through foaming, bacteria were entrapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 40 publications
(60 reference statements)
1
48
0
Order By: Relevance
“…The applications range from wastewater treatment [1,2], to electrode material in lithium ion batteries [3][4][5], magnetic fluids respectively ferrofluids [6][7][8], used e.g. as magnetic inks for jet printing [9,10], biosensing applications [11,12], medical applications, such as targeted drug delivery [13,14], contrast agents in magnetic resonance imaging [15][16][17][18][19][20], and also biotechnological processing [21][22][23][24] and carrier materials for biocatalysts [25], to sum up a few. All of these applications require high magnetization values and a narrow particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The applications range from wastewater treatment [1,2], to electrode material in lithium ion batteries [3][4][5], magnetic fluids respectively ferrofluids [6][7][8], used e.g. as magnetic inks for jet printing [9,10], biosensing applications [11,12], medical applications, such as targeted drug delivery [13,14], contrast agents in magnetic resonance imaging [15][16][17][18][19][20], and also biotechnological processing [21][22][23][24] and carrier materials for biocatalysts [25], to sum up a few. All of these applications require high magnetization values and a narrow particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the capacity for rhamnolipid production by both free and alginate-entrapped cells of Pseudomonas fl uorescence was investigated in batch cultures, and it was confi rmed that immobilization increased the biosurfactant recovery (Abouseoud et al, 2008). Heydl et al (2011) reported a new integrated process for continuous rhamnolipid production by Pseudomonas aeruginosa DSM 2874 entrapped in magnetic alginate beads, reaching a fi nal amount of 70 g rhamnolipid after four production cycles in a 10-l bioreactor.…”
Section: Discussionmentioning
confidence: 99%
“…Winterburn et al [12] developed an FCFS setup for continuously recovering extracellular biosurfactants from fermenters to foam separation column. Heyd et al [3] reported that bacteria could be entrapped in magnetic alginate beads to prevent loss of the cell through foaming. Cui et al [13] developed a technology of fermentation coupling with foam fractionation and membrane module.…”
Section: Introductionmentioning
confidence: 99%
“…[1] As well as other separation technologies, foam separation can be used as an in situ product removal technology. [2][3][4] Comparing with classic separation technologies, such as extraction, ion-exchange adsorption, evaporation, and membrane separation, foam separation has many advantages: first of all, foam is milder than organic solvent. Thus, it avoids the loss of biomass because of organic solvent toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation